Physiological and transcriptomic analyses reveal the mechanism of improved mango storage by pre-harvest GA₃ and CPPU treatment - Tang-xin Jiang; Bi-xia Wang; Zhi-xi He; Jing-tang Zhang; Cong Luo; Xin-hua He (Postharvest Biology and Technology, 2027)

Study on the diffusion and explosion characteristics of hydrogen leakage incident in tunnel under longitudinal ventilation - Haiyong Cong; Gaoming Lu; Zhuyu Shao; Hairuo Hu; Yubo Bi (Tunnelling and Underground Space Technology, 2026)

Experimental investigation on smoke control and smoke extraction efficiency of two-point extraction system under longitudinal sloped tunnel fires - Zhuyu Shao; Mingshu Bi; Haiyong Cong; Luyang Liu; Fengnan Sun; Yubo Bi; Tianjiao Zhang (Tunnelling and Underground Space Technology, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

Treatment of aquaculture wastewater by co-cultivation of Chlorella vulgaris and its phycosphere-associated bacteria - Dajuan Zhang; Qipeng Wang; Shulin Zhang; Fangdi Cong; Mengmeng Cao; Xiangdong Bi (Aquaculture, 2026)

Episodic tropical cyclones dominate cross-shelf sediment transport in the East China Sea - Shuai Cong; Xiao Wu; Jianzhong Ge; Yunhai Li; Naishuang Bi; Houjie Wang (Marine Geology, 2026)

Tissue-Resident Macrophage PIEZO1 Transduces Mechanical Stress into Inflammatory Pain in Acute Gout - Tianyi Shen; Ting Wang; Liyan Wu; Zihan Wang; Liqin Gan; Yubin Luo; Cong Liu; Yang Xu; De-An Guo; Qirui Bi; Wanying Wu; Lvyi Chen; et al. (Neuroscience Bulletin, 2026)

Conversion of polyethylene to monoaromatics via a tandem catalytic strategy - Zhiye Ma; Ziyu Cen; Tianrui Bi; Weilong Wen; Cong Luo; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Qinglei Meng; Huizhen Liu; Longfei Lin; Buxing Han (Science Bulletin, 2026)

Tropical cyclone catalyzes seasonal transition of marginal sea: premature dissipation of cold pool - Yanhao Liu; Houjie Wang; Xiao Wu; Shuai Cong; Xiaozhou Ruan; Zengrui Rong; Naishuang Bi; Zuosheng Yang (Ocean Modelling, 2026)

Mechanical control of invasive vegetation in China promotes tidal channels development: A case study of the Yellow River mouth wetland - Qi Ba; Shuai Cong; Yupeng Ren; Yirui Shi; Xiao Wu; Houjie Wang; Naishuang Bi (Geomorphology, 2026)

Solidago canadensis alters rhizosphere bacterial communities of Artemisia argyi under warming and nitrogen deposition—invaded rhizospheres become similar to the invader's - Yong-Feng Wang; Yun-Long Zhang; Ying Li; Guang-Qian Ren; Shan-Shan Qi; Bi-Ying Zhao; Zhi-Cong Dai; Dao-Lin Du (Plant and Soil, 2026)

Nanoparticle-free dualmodal lateral flow immunoassay for sensitive detection of aflatoxin B1 based on “four-in-one” multifunctional nanobody - Tingting Gong; Weili Shen; Kaiyuan Chen; Meng Bi; Cong Liu; Hao Zheng; Wenjia Niu; Yulin Mao; Changli Shao; Longlong Luo; Tieqiang Sun (Analytica Chimica Acta, 2026)

United-modality underwater object tracking via distinct enhancing and high-dimensional fusion - Kaixiang Yan; Wenhua Qian; Cong Bi; Jie Liu (Ocean Engineering, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

RAGE deficiency ameliorates abdominal aortic aneurysm progression - Cong Bi; Bingqi Liu; Peixian Gao; Chuanle Wang; Sheng Fang; Zhengkun Huo; Qingpeng Song; Dianning Dong; Xuejun Wu; Gang Li (Inflammation Research, 2025)

The climate-driven mechanisms of sedimentary evolution in the mud area southwest off Cheju Island during the Holocene - Jingyi Cong; Huisong Fan; Shipu Bi; Xi Mei; Yanguang Dou; Zhonglei Wang; Ze Ning; Yong Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Particulate organic carbon dynamics off the Yellow River Estuary revealed by in-situ hydrodynamics and carbon isotopes - Taian Lu; Thomas S. Bianchi; Naishuang Bi; Xiao Wu; Shuai Cong; Jinya Xu; Xiaoyan Ning; Houjie Wang (Marine Geology, 2025)

Advanced capacitive deionization technology for selective removal of per- and polyfluoroalkyl substances: High selective adsorption capacity and efficient recovery - Lu Zhang; Wenbo Bi; Baohua Wang; Taiwen Chen; Lei Zhao; Ying Lyu; Cong Lyu (Chemical Engineering Journal, 2025)

On-site identification of black soil thickness based on drill-core imaging and deep learning - Lei Qiao; Jiabao Zhang; Xicai Pan; Rutian Bi; Jienan Xu; Cong Tang; Kwok Pan Chun (CATENA, 2025)

High-throughput screening of acetals/ketals in edible essences via GC-Orbitrap-MS and their formation rates at room temperature - Xiaoyu Wang; Qiong Guo; Lining Pan; Cong Nie; Yiming Bi; Yaqiong Qin; Fuwei Xie; Fangqi Du; Yuhan Peng; Bing Wang; Ruihong Liu; Hui Wang; et al. (Food Chemistry, 2025)

Environmental and provenance variations in borehole core CSH-01B from the western edge of the North Yellow Sea: Responses to tectonic movements since the late pliocene - Zhi-Xian Tian; Yong Zhang; Wei Xiong; Bei-Bei Mi; Zhong-Lei Wang; Shi-Pu Bi; Jing-Yi Cong; Xi Mei (Quaternary Science Reviews, 2025)

Impact of seasonal variations in fronts on suspended sediments transport off the coastal area of Fujian Province - Biying Xue; Yong Zhang; Houjie Wang; Yanguang Dou; Xiao Wu; Shipu Bi; Jingyi Cong; Gang Hu (Continental Shelf Research, 2024)

VCAT: an integrated variant function annotation tools - Bi Huang; Cong Fan; Ken Chen; Jiahua Rao; Peihua Ou; Chong Tian; Yuedong Yang; David N. Cooper; Huiying Zhao (Human Genetics, 2024)

An efficient and robust real-time longitudinal ventilation control method for unpredictable tunnel fire scenarios - Hairuo Hu; Haiyong Cong; Zhuyu Shao; Yiping Zeng; Yubo Bi; Jinghao Liu (Tunnelling and Underground Space Technology, 2024)

Intensified O2 activation and lattice O supply at inverse oxide-metal interface for catalytic oxidation reactions: A case study in alcohol oxidation - Kun Liu; Yongbin Sun; Jiaqi Si; Cong Fu; Yushui Bi; Xiaomin Zhao; Guofeng Zhao (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Construction of ultrafine and highly dispersed RuSe2 on WOx by “atom-to-cluster” strategy for efficient hydrogen evolution reaction - Fengyue Sun; Wenjing Bao; Chao Feng; Jiahui Bi; Changle Yue; Cong Zhang; Na Liu; Haoyuan Hao; Yukun Lu (Fuel, 2024)

Hybrid ion/electron interfacial regulation stabilizes the cobalt/oxygen redox of ultrahigh-voltage lithium cobalt oxide for fast-charging cyclability - Zhihong Bi; Anping Zhang; Gongrui Wang; Cong Dong; Pratteek Das; Xiaoyu Shi; Zhong-Shuai Wu (Science Bulletin, 2024)

Experimental investigation on flame morphology and wall-attached flame temperature of jet flame under the coupled effect of nozzle angle and nozzle-wall spacing - Gaoming Lu; Haiyong Cong; Ziqi Yuan; Zhuyu Shao; Lili Ye; Yubo Bi; Mingshu Bi; Binshan Yu (Fuel, 2024)

Corrigendum to “Comparing the mechanisms of two types of summer extreme precipitation in Beijing-Tianjin-Hebei region, China: Insights from circulation patterns and moisture transports” [Atmospheric Research, 302 (2024), 107304] - Jing Cong; Huijun Liu; Guicai Ning; Hong Chen; Xueyan Bi; Bo Liu; Yuanjian Yang; Haiyun Xia (Atmospheric Research, 2024)

Comparing the mechanisms of two types of summer extreme precipitation in Beijing-Tianjin-Hebei region, China: Insights from circulation patterns and moisture transports - Jing Cong; Huijun Liu; Guicai Ning; Hong Chen; Xueyan Bi; Bo Liu; Yuanjian Yang; Haiyun Xia (Atmospheric Research, 2024)

Experimental study on the performance of synergistic ventilation system combining shaft with mechanical ventilation in extra-long road tunnels - Bin Zhu; Haiyong Cong; Binshan Yu; Zhuyu Shao; Lili Ye; Yubo Bi; Yiping Zeng (Tunnelling and Underground Space Technology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Molecular characterization and functional analysis of peroxiredoxin 1 (Prx1) from roughskin sculpin (Trachidermus fasciatus) - Yingying Liu; Haiyan Cong; Caihong Bi; Haidong Zha; Shanshan Yu; Lihua Zhao; Qian Zhu (Fish Physiology and Biochemistry, 2024)

Crosstalk between methanogens and methanotrophs determines methane emissions in a rice paddy under different watering regimes - Xianxian Zhang; Zuopeng Lv; Huifeng Sun; Junguo Bi; Jining Zhang; Cong Wang; Sheng Zhou (Applied Soil Ecology, 2024)

General models of buoyant sidewall flame morphology affected by crossflows on the inclined surface based on the mirror approach - Yubo Bi; Zhian Yang; Jiaqi Wang; Shenshi Huang; Haiyong Cong; Lili Ye; Mingshu Bi (Fuel, 2024)

Improving enzyme accessibility in the aqueous enzymatic extraction process by microwave-induced porous cell walls to increase oil body and protein yields - Xin Guo; Bi-cong Wu; Yun Jiang; Yu Zhang; Bo Jiao; Qiang Wang (Food Hydrocolloids, 2024)

Interplay of shell evolution and oxidation depth on the ignition and combustion behavior of aluminum nanoparticles - Yiming Lu; Lili Ye; Fan Wang; Lei Zhang; Yubo Bi; Haiyong Cong; Mingshu Bi (Fuel, 2023)

Intermittent migration of mixing front driven by typhoon events on the inner shelf of the East China Sea: A FVCOM modeling study - Shuai Cong; Xiao Wu; Jianzhong Ge; Naishuang Bi; Yunhai Li; Jian Lu; Houjie Wang (Marine Geology, 2023)

Rapid oscillation of sediment transport between the Bohai Sea and the Yellow Sea induced by Typhoon Lekima (2019) - Yanhao Liu; Houjie Wang; Shuai Cong; Zhengchen Zang; Naishuang Bi; Changwei Bian; Jianzhong Ge; Xiao Wu (Marine Geology, 2023)

Study on the inhibitory effect and mechanism of perfluoro(2-methyl-3-pentanone) on the combustion of gasoline blended with biomass additives - Xuemeng Mu; Haiyong Cong; Ziqi Yuan; YuBo Bi; Mingshu Bi (Fuel, 2023)

Involvement of the heat shock response (HSR) regulatory pathway in cadmium-elicited cerebral damage - Milton Talukder; Shao-Shuai Bi; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2023)

A new method for long-term in situ monitoring of seabed interface evolution: A self-potential probe - Zhihan Fan; Xianming Zhu; Haibo Xu; Zhiwen Sun; Hong Zhang; Xianbin Bi; Cong Hu; Dequan Lu; Zhongqiang Sun; Kai Li; Yongzheng Quan; Yonggang Jia (Ocean Engineering, 2023)

Investigating food web structure and system function of an artificial reef ecosystem based on carbon and nitrogen stable isotope analysis: implications for reef management - Jie Feng; Xiaolong Zhao; Fan Bi; Wei Zhao; Liang Zhao; Hao Song; Meijie Yang; Zhi Hu; Cong Zhou; Pu Shi; Pengpeng Hu; Peizhen Ma; et al. (Frontiers in Marine Science, 2023)
Introduction Food web is an important basis for identifying trophodynamic processes, and evaluating the structural and functional characteristics of ecosystems. The trophodynamics and system function of artificial reef (AR) ecosystems have rarely been examined. Methods Stable isotope analysis was used to investigate the food web structure and functions of an artificial reef (AR) ecosystem in this study. Results and Discussion The δ13C and δ15N values of particulate organic matter (POM) in AR showed noticeable seasonal changes, and the δ13C value of POM in autumn was significantly higher than that in other seasons (p<0.05). There were no significant seasonal variations in the δ13C values of solid organic matter (SOM), and no significant difference between SOM and POM was observed except in autumn. Moreover, macroalgae did not significantly affect the δ13C values of SOM. Phytoplankton may be the primary nutrient source in the AR ecosystem. The δ13C values of most crustaceans in the AR were approximately between (-17.03 ± 0.22) ‰ – (-17.74 ± 0.07) ‰, higher than those of most fish, indicating that they may have different basal nutrient sources. The trophic level (TL) of invertebrates was between 2.00 and 3.09, and that of fish was between 2.98 and 3.66. The distribution of δ13C and TLs of crustaceans and fish showed that, except for crustaceans, bivalve shellfish and zooplankton might also be important food sources for fish in the AR ecosystem. Conclusion The δ13C and δ15N values of most species in the AR showed good continuity, indicating that they may be mainly produced from the AR ecosystem. Migratory species such as Lateolabrax japonicus and Sepiella maindroni showed higher δ13C values, indicating that they may have migrated from other sea areas. To maintain the stability of the ecosystem structure and function of the AR ecosystem, fishing activities should be carried out following the maximum sustainable yield theory. Future research needs to identify the nutritional relationship between AR and its adjacent sea areas, to depict the food web structure of the AR with higher accuracy.

Purification performance from bypass ecological treatment systems treating WWTPs effluents and improvement of water quality in receiving rivers: A case study in southern China - Xiaoxu Zheng; Shengjun Xu; Yeliang Bi; Gong Cheng; Shuanglong Ma; Hao Zhang; Cancan Jiang; Cong Wang; Ping Lyu; Yu Qin; Xuliang Zhuang (Journal of Environmental Management, 2023)

The Depletion of NAMPT Disturbs Mitochondrial Homeostasis and Causes Neuronal Degeneration in Mouse Hippocampus - Chen Shen; Cong Chen; Tong Wang; Tong-Yao Gao; Min Zeng; Yun-Bi Lu; Wei-Ping Zhang (Molecular Neurobiology, 2023)

An experimental study and mathematical quantification of buoyant turbulent flame morphology under the coupling effects of inclined surfaces and crossflows - Yubo Bi; Zhian Yang; Haiyong Cong; Lili Ye; Mingshu Bi (Fuel, 2023)

Investigation and improvement of the Mini-Max Polynomial Approximation method for solving burnup equations - Cong Zhang; Binhang Zhang; Yanzhao Bi; Xianbao Yuan; Yonghong Zhang; Haibo Tang (Annals of Nuclear Energy, 2023)

Cerebellar injury induced by cadmium via disrupting the heat-shock response - Shao-Shuai Bi; Milton Talukder; Xue-Tong Sun; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2022)

Cadmium Through Disturbing MTF1-Mediated Metal Response Induced Cerebellar Injury - Shao-Shuai Bi; Milton Talukder; Hai-Tao Jin; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Neurotoxicity Research, 2022)

Estimation of Active Earth Pressure for Limited Width of Soil Using Nonlinear Failure Criterion - Lu Cong; Xuan-yu Yang; Bi-chang Zhang; Wei Xiong (Geotechnical and Geological Engineering, 2022)

Hydrodynamic and Flow Field Characteristics of Water Jet Propulsion under Mooring Conditions - Dagang Zhao; Yang Zhang; Qian He; Cong Sun; Mingqi Bi (Journal of Marine Science and Engineering, 2022)
The acceleration characteristics of a water jet-propelled ship during startup are related to its performance under mooring conditions. Water jet propulsion cavitation during startup increases the vibration and noise of the whole ship. Therefore, accurately predicting and analyzing the performance, hydrodynamics and flow field characteristics of water jet-propelled ships under mooring conditions can help elucidate the startup characteristics of the ships and optimize their acceleration strategies. In this study, the hydrodynamic and flow field characteristics of water jet propulsion and water jet propulsion ships under mooring conditions were studied using three-dimensional numerical modeling. First, the hydrodynamic performance of the water jet propeller was analyzed, and the relevant flow field law was derived. Then, the hydrodynamic performance, internal and external flow field characteristics, pulsation pressure and flow rate at the nozzle, and pulsation pressure at the monitoring points around the impeller of the water jet propulsion ship model were analyzed under mooring conditions. We obtained the open-water law for the water jet propeller and the hydrodynamic force and flow field law for a two-pump water jet propulsion ship. The ship model developed in this study provides a good theoretical foundation for further research on water jet propulsion.

Estimate greenhouse gas emissions from water-saving and drought-resistance rice paddies by deNitrification-deComposition model - Xianxian Zhang; Huifeng Sun; Junguo Bi; Bo Yang; Jining Zhang; Cong Wang; Sheng Zhou (Clean Technologies and Environmental Policy, 2022)

The sensitivity of numerical simulation to vertical mixing parameterization schemes: a case study for the Yellow Sea Cold Water Mass - Congcong Bi; Zhigang Yao; Xianwen Bao; Cong Zhang; Yang Ding; Xihui Liu; Junru Guo (Journal of Oceanology and Limnology, 2021)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

An Interactive Integrated Interpretation of GPR and Rayleigh Wave Data Based on the Genetic Algorithm - Tan Qin; Yonghui Zhao; Shufan Hu; Cong An; Wenda Bi; Shuangcheng Ge; Lorenzo Capineri; Thomas Bohlen (Surveys in Geophysics, 2020)

Observed characteristics of tidal currents and mean flow in the northern Yellow Sea - Congcong Bi; Xianwen Bao; Yang Ding; Cong Zhang; Yu Wang; Biao Shen; Kai Wan (Journal of Oceanology and Limnology, 2019)

A numerical study of the South China Sea Warm Current during winter monsoon relaxation - Cong Zhang; Yang Ding; Xianwen Bao; Congcong Bi; Ruixiang Li; Cunjie Zhang; Biao Shen; Kai Wan (Journal of Oceanology and Limnology, 2018)

The Transcriptome Study of Subtype M2 Acute Myeloblastic Leukemia - A-yang Wu; Hui-cong Yang; Cong-meng Lin; Bi-de Wu; Qi-shui Qu; Yuan-hai Zheng; Hua Wei; Xu-qiao Mei; Zhen-hua Zeng; Xu-dong Ma (Cell Biochemistry and Biophysics, 2015)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Large-scale analysis of phosphorylated proteins in maize leaf - Ying-Dong Bi; Hong-Xia Wang; Tian-Cong Lu; Xiao-hui Li; Zhuo Shen; Yi-Bo Chen; Bai-Chen Wang (Planta, 2011)

Comparative temporal analyses of the Pinus sylvestris L. var. mongolica litv. apical bud proteome from dormancy to growth - Ying-Dong Bi; Zhi-Gang Wei; Zhuo Shen; Tian-Cong Lu; Yu-Xiang Cheng; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2011)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)